Perbandingan keefektifan antara konseling profesional dengan konseling sebaya (peer counseling) - As saidah, Filda Fuady; Himamie, Rushoyfah (Maliki Interdisciplinary Journal, 2023)
Counseling services are needed to help solve problems for individuals, especially among adolescents who often experience various kinds of problems. The purpose of this research is to compare the effectiveness of peer counseling with professional counselors. The research method used is the library search method which is described descriptively. The results of this study indicate that both counselors can be said to be effective, depending on the counseling needs of each.